THE EFFECTIVENESS OF INTRADIALYTIC EXERCISE AEROBIC ON SLEEP QUALITY OF CHRONIC RENAL FAILURE PATIENTS THROUGH HEMODIALYSIS: A SYSTEMATIC LITERATURE REVIEW AND META-ANALYSIS (Proceedings OPTIMAL, 2025)
The chronic renal failure undergoing hemodialysis increases 7% annually causing sleep disorders is more prevalence in adults by 45% to 80%. Aerobic exercise which is non-pharmacological nursing interventions is known as an approach to overcome sleep disorder in chronic renal failure patients. The aim in this study is to review the relevant studies in the effectiveness of intradialytic exercise aerobic to address sleep quality in patients with renal failure undergoing hemodialysis. This research method uses literature searches sourced from ProQuest, PubMed, NCBI, and google scholar with a total of 86 articles and 20 articles that are worth analyzing, the analysis was carried out using Review Manager 5.4. with a 95% confidence level, heterogeneity between studies was assessed using a statistical test with the chi-test, using a random-effects model. The studies in the Asian continent showed that the treatment on patients (2 hours of dialysis with a duration of ≤ 60 minutes) that have characteristics ≥ 3 months undergone HD, resulted high heterogeneity value by chi = 1109494.75. The sleep quality was measured by Pittsburgh Sleep Quality Index (PSQI) instrument. Moreover, the intradialytic exercise evidently improved sleep quality (p-Value